Childhood asthma. A controlled trial of family psychotherapy. Issue 2 (February 1979) - Lask, B; Matthew, D
Abstract : In an attempt to evaluate the effectiveness of family psychotherapy as an adjunct conventional treatment in childhood asthma, children with moderate to severe asthma were randomly allocated to a control group or to an experimental group; the latter group received 6 hours of family treatment during a 4-month period, and both groups had standard medical treatment. While there was no significant difference between the two groups on three parameters, the experimental group were significantly better in day-wheeze score and thoracic gas volume. These results suggest that family treatment in selected cases may have a place in the overall management of childhood asthma, and that more research with larger numbers of children is necessary.